Neo-Romantic concepts of imagination in Croatian National Revival writings and in Croatian War of Independence poetry - Žužul, Ivana (Poznańskie Studia Slawistyczne, 2011)
The paper attempts to shed light on the concept of imagination and its formative role in imagining collective identities such as gender, religion or nation in literary, journalistic and programmatical texts written by Croatian revivers, as well as in the poetry of the Croatian War of Independence. Here, the concept of imagination is conceived as a field criss-crossed by contradictions selectively used by the revivers and contemporary Croatian poets in the 1990's, in order to achieve certain political goals. According to need, they use it to reconcile resemblances with differences, general with particular or else for the purpose of generating hegemonistic symbols or organic unity of culture/nation, they erase divisions, ignoring and abolishing othernesses.